Legal Framework for Banking Activities in Digital Enviroment. A Case Study of Vietnam - Cao, Cao Dinh Lanh (PRAWO i WIĘŹ, 2025)
The objective of the article is to analyze and evaluate the legal aspects of banking activities in the digital environment in Vietnam in three areas: i) the legal framework regulating electronic transactions in the banking sector; ii) the controlled testing mechanism for financial technology in the banking sector; and iii) the protection of personal data in banking activities. Based on these findings, the study also highlights certain implications for ensuring requirements for risk control, protection  the interests of stakeholders, and business operations of banks in Vietnam.